Determinants of Consumer Willingness to Purchase Non-Deceptive Counterfeit Products and the European Union - Irena Vida
This study offers insights into non-deceptive counterfeiting by focusing on consumers in a new EU member country. More specifically, consumers’ inclination to purchase counterfeits at various price levels relative to retail prices of genuine branded products is examined, and the effects of various socio-economic and socio-psychological characteristics are explored. In reviewing the consumer behavior literature and recent empirical work, a conceptual model of consumer general willingness to purchase counterfeit products was developed. Using path analyses to test the system of structural relationships among the variables, inconsistent patterns of results were found across three classes of counterfeit products. Implications for management and further research are provided.counterfeit products, consumer unethical behavior, willingness to buy, Slovenia